Hyperhomocysteinemia induced by excessive methionine intake promotes rupture of cerebral aneurysms in ovariectomized rats. Issue 1 (December 2016) - Korai, Masaaki; Kitazato, Keiko; Tada, Yoshiteru; Miyamoto, Takeshi; Shimada, Kenji; Matsushita, Nobuhisa; Kanematsu, Yasuhisa; Satomi, Junichiro; Hashimoto, Tomoki; Nagahiro, Shinji
Abstract Background Hyperhomocysteinemia (HHcy) is associated with inflammation and a rise in the expression of matrix metalloproteinase-9 (MMP-9) in the vascular wall. However, the role of HHcy in the growth and rupture of cerebral aneurysms remains unclear. Methods Thirteen-week-old female Sprague-Dawley rats were subject to bilateral ovariectomy and ligation of the right common carotid artery and fed an 8 % high-salt diet to induce cerebral aneurysms. Two weeks later, they underwent ligation of the bilateral posterior renal arteries. They were divided into two groups and methionine (MET) was or was not added to their drinking water. In another set of experiments, the role of folic acid (FA) against cerebral aneurysms was assessed. Results During a 12-week observation period, subarachnoid hemorrhage due to aneurysm rupture was observed at the anterior communicating artery (AcomA) or the posterior half of the circle of Willis. HHcy induced by excessive MET intake significantly increased the incidence of ruptured aneurysms at 6–8 weeks. At the AcomA of rats treated with MET, we observed the promotion of aneurysmal growth and infiltration by M1 macrophages. Furthermore, the mRNA level of MMP-9, the ratio of MMP-9 to the tissue inhibitor of metalloproteinase-2, and the level of interleukin-6 were higher in these rats. Treatment with FA abolished the effect of MET, suggesting that the inflammatory response and vascular degradation at the AcomA is attributable to HHcy due to excessive MET intake. Conclusions We first demonstrate that in hypertensive ovariectomized rats, HHcy induced by excessive MET intake may be associated with the propensity of the aneurysm wall to rupture.